The effect of salinity and mangrove age on the community structure of mangrove associated bivalves in Barrido, Ajuy, Iloilo. - Tupino, Juan Florencio Tumenlaco
This study documents the commercially important species of bivalves at Barangay Barrido, Ajuy which can be a reference for future studies. It also describes the effect of salinity, mangroves, mangrove age and sediment characteristics on the density and distribution of bivalves. Overall, four families of bivalves which include Veneridae, Mytilidae, Ostereidae and Psammobiidae have been recorded in Barrido, Ajuy. Seven species of bivalves have been identified. These include; Galfrarium tumidum, Ruditapes variegatus, Katelysia hiantina (all under Veneridae), Septifer bilocularis, Modiulus aratus (the two under Mytilidae), Saccostrea cucullata (Ostreidae), Asaphis violascens (Psammobiidae). The density and distribution of the dominant species of bivalves are affected by the interplay of several factors. Reforested mangrove areas with high salinity and organic matter content and finer sediments are associated with high bivalve density. The results of the effect of mangrove age are not taken to effect the true picture due to lack of age diference between compared sites. Further study regarding this matter is therefore recommended.